Ignorance Is Not Bliss: A U.K. Study of Sexual and Domestic Abuse Awareness on Campus, and Correlations With Confidence and Positive Action in a Bystander Program - Bovill, Helen (Journal of interpersonal violence, 2022)
This article reports on a U.K. research study encompassing two surveys which used evidence-based scales of awareness, confidence to intervene, and intervention opportunities and action regarding sexual and domestic abuse on campus. They were sent to all first-year incoming undergraduates (>n = 7,000) at one post-1992 U.K. university and received n = 1,604 responses. The study finds that survey respondents demonstrated low awareness of sexual and domestic abuse as a problem on campus. In the analysis of Survey 2, respondents were divided into three groups, those receiving active intervention, passive intervention, and no intervention from a university social norms marketing campaign challenging abuse on campus. The study drives the field forward by considering how confidence to act mediates the relationship between awareness and positive action. It finds associations between active intervention and raised awareness that is not noted in passive or no intervention. Active intervention potentially brings together the mediating variable of confidence where awareness + confidence = positive action. This article makes recommendations for first-year incoming undergraduates to receive awareness raising information about sexual and domestic abuse, prior to coming to university. Universities may also consider working with schools to counter a lack of awareness, which may emanate from normalization discourses learnt prior to coming to university and perpetuated once there. Managing low awareness of sexual and domestic abuse should be a priority of bystander programs and some form of active intervention is potentially beneficial as early as possible in university student journeys.